1979
DOI: 10.1159/000153033
|View full text |Cite
|
Sign up to set email alerts
|

A New Method for the Analysis of Age Trends in CPK Levels with Application to Duchenne Muscular Dystrophy

Abstract: Measurement of serum creatine phosphokinase (CPK) is the most commonly applied test for carrier detection in Duchenne muscular dystrophy. About two thirds of all carriers have markedly elevated CPK levels. Age correction of CPK measurements would be straightforward if carriers of all ages could be unambiguously identified. Since such identification is impossible, we elaborate an indirect statistical method which is based on Haldane’s theory of the balance between selection and mutation for X-linked lethals. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1981
1981
1998
1998

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…Our results indicate that: (a) in accord ance with the above reports, both CK and PK levels are higher among younger heter ozygotes than in adults; (b) these levels de crease steadily with age in a linear fashion, as predicted by the regression formula de rived by Lange and Zatz [1979] in relation to CK, and (c) this effect is much more evi dent among young heterozygotes than in normal children and adolescents, since the correlation coefficients obtained in our previous study of normal children were around -0.3 [Passos et al, 1985].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our results indicate that: (a) in accord ance with the above reports, both CK and PK levels are higher among younger heter ozygotes than in adults; (b) these levels de crease steadily with age in a linear fashion, as predicted by the regression formula de rived by Lange and Zatz [1979] in relation to CK, and (c) this effect is much more evi dent among young heterozygotes than in normal children and adolescents, since the correlation coefficients obtained in our previous study of normal children were around -0.3 [Passos et al, 1985].…”
Section: Discussionsupporting
confidence: 87%
“…Similar results were also reported by Lane and Roses [1981]. Lange and Zatz [1979] found for the group of DMD carriers a linear regres sion that could explain the age-related de crease in serum CK levels. However, no significant decrease in serum CK activity was detected in a follow-up study of 16 possible and obligate adult carriers , A decrease in serum PK levels with age in DMD carriers has been suggested by Percy et al [1979] and Griggs et al [1985].…”
Section: Introductionsupporting
confidence: 90%
“…To transform the data to normality, a double (natural) logarithmic transformation was applied to the CK values. Lange and Zatz [1979] have shown that taking the logarithm of the CK value was sufficient to eliminate skewness and kurtosis, yet the variance of CK remained 5.94 times as high in the carriers as in controls. Thus to approach homoscedasticity the more severe transform was applied.…”
Section: Standardization Of Creatine Kinase Measurementsmentioning
confidence: 99%
“…The observation that serum CK decreases with age in young carriers [Thompson et al, 1967;Moser and Vogt, 1974;Lange and Zatz, 1979;Passos-Bueno et al, 1989; the present study] has suggested that this might occur due to the progressive elimination of dystrophic fibers which contribute to the release of serum enzymes to the blood. However, before DNA analysis it was not possible to determine if a female was an obligate carrier of the DMD gene before the birth of an affected child.…”
Section: Serum Ck In Dmd Carriersmentioning
confidence: 50%
“…In affected male DMD/Becker muscular dystrophy (BMD) patients, it was shown that the activity of CK in serum gradually decreases with advancing age due to the progressive elimination of dystrophic fibers [Pennington, 1980;Rowland, 1980;Edwards et al, 1983;Hoffman et al, 1987Hoffman et al, , 1988Zatz et al, 1991]. It was suggested by us and others, that the serum CK activity in female heterozygotes seems to decrease also with age due to the same mechanism observed in affected boys [Dreyfus et al, 1966;Thompson et al, 1967;Lange and Zatz, 1979;Zatz et al, , 1998Passos-Bueno et al, 1989]. However, in the premolecular era it was not possible to identify among young ''at-risk'' females those who were obligate carriers of the DMD mutated gene.…”
Section: Introductionmentioning
confidence: 91%